2019
DOI: 10.1021/acscatal.9b03623
|View full text |Cite
|
Sign up to set email alerts
|

CoP Nanoframes as Bifunctional Electrocatalysts for Efficient Overall Water Splitting

Abstract: Transition-metal phosphides have been shown to be promising electrocatalysts in water for both hydrogen evolution reaction (HER) and oxygen evolution reaction (OER). To maximize reactivity toward both entails limiting the catalyst size while maintaining reactivity and avoiding aggregation. Frame-like hollow nanostructures (nanoframes) provide the required open structure with sufficient channels into the interior volume. We demonstrate here the design and synthesis of CoP nanoframes (CoP NFs) by a strategy invo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
225
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 412 publications
(233 citation statements)
references
References 39 publications
8
225
0
Order By: Relevance
“…[4][5][6] The negatively charged P atoms in TMPs can not only capture protons as Lewis bases, but also effectively promote the desorption of H 2 from the active sites. Particularly, recent studies have shown that cobalt phosphides could act as bifunctional catalysts toward HER and OER, [7,8] through heteroatoms doping, [9,10] MOF coupling, [11,12] anodic electrochemical treating, [13] and hetero-structure engineering. [14] Preparation of cobalt phosphides generally involves two key procedures.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] The negatively charged P atoms in TMPs can not only capture protons as Lewis bases, but also effectively promote the desorption of H 2 from the active sites. Particularly, recent studies have shown that cobalt phosphides could act as bifunctional catalysts toward HER and OER, [7,8] through heteroatoms doping, [9,10] MOF coupling, [11,12] anodic electrochemical treating, [13] and hetero-structure engineering. [14] Preparation of cobalt phosphides generally involves two key procedures.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, transition metal phosphides, especially bimetallic transition metal phosphides have attracted significant attentions as bi-functional electrocatalysts for water-splitting owing to their remarkably enhanced catalytic activities [32,33]. To maximize the electrochemical performance of the catalysts, endowing the electrocatalysts with hollow nanostructures is regarded as an effective approach, which can significantly increase their specific surface areas and expose more reactive sites [34][35][36][37]. Moreover, the ion diffusion length and transport resistance for water splitting can be effectively reduced by their large void spaces, which has been fully demonstrated by previous studies [38][39][40].…”
Section: Introductionmentioning
confidence: 99%
“…The performance for the NiCo-CeO 2 ||NiCo(OH) x -CeO 2 electrolyzer also outperforms most recently reported electrolyzers based on non-noble bifunctional electrocatalysts (Figure 5e; Table S4, Supporting Information). [45][46][47][48][49][50][51][52][53][54][55][56][57][58][59] The excellent overall water splitting activity of the NiCo-CeO 2 ||NiCo(OH) x -CeO 2 electrolyzer is not only attributed to the high intrinsic catalytic activities of NiCo-CeO 2 / GP and NiCo(OH) x -CeO 2 /GP, but also to the self-supported electrode structure. Due to the in situ growth of active species on conductive substrate, the interface resistances of the self-supported NiCo-CeO 2 /GP and NiCo(OH) x -CeO 2 /GP electrodes are greatly lower than those of the Pt/C(20%)/GP and RuO 2 /GP electrodes by physically coating (Figure S25, Supporting Information), which are conducive to the rapid electron transfer.…”
Section: Resultsmentioning
confidence: 99%
“…The performance for the NiCo–CeO 2 ||NiCo(OH) x –CeO 2 electrolyzer also outperforms most recently reported electrolyzers based on non‐noble bifunctional electrocatalysts (Figure 5e; Table S4, Supporting Information). [ 45–59 ]…”
Section: Resultsmentioning
confidence: 99%